(untitled) (International Seven Journal of Health Research, 2024)
Visceral leishmaniasis, known as kala-azar, is an important global public health issue, especially in developing countries such as Brazil. Transmission is influenced by precarious socio-environmental conditions, with Maranhão standing out as an area of concern due to the high prevalence and lethality of untreated cases. The etiological agent is the protozoan Leishmania, transmitted by the straw mosquito and affecting both wild and domestic hosts, such as dogs. The study analyzes the relationship between socio-environmental factors and the occurrence of the disease, highlighting the need for prevention strategies to reduce its prevalence and incidence, focusing on health education and changes in habits.